Clientelist Mobilization and Political Participation Outside of the Electoral Arena - Holzner, Claudio A. (Revista Latinoamericana de Opinión Pública, 2023)
Scholarship on clientelist mobilization has focused almost exclusively on electoral clientelism, that is efforts by patrons and brokers to encourage turnout and participation in campaign rallies. What is less well understood is the impact of clientelist mobilization on other modes of political participation, like protest activity and citizen claim making. To fill this gap, I use LAPOP survey data from 2010 and 2014 to explore the relationship between vote-buying and nonelectoral forms of political activity. Despite the expectation by many that collective action and clientelist mobilization are incompatible, this study finds a strong relationship between vote-buying efforts and participation in protests in most of Latin America. Similarly, people who receive vote-buying offers are much more likely to engage in claim-making activities. I explore the mechanisms through which clientelism encourages political activism, highlighting ways that clientelist networks work through civic organizations and foster stronger partisan identities and greater political engagement.